Processo para gerenciar a integração de clientes no processo de desenvolvimento do produto - González, Mario Orestes Aguirre (Universidade Federal de São Carlos, 2010)
Understanding customer needs is considered, in the literature of management product development process, one of the major critical success factors of a new product. However, current researches highlight those traditional methods for lifting these needs show deficiency, especially those latent needs. It has emerged, therefore, theories that seek to improve this situation as: product development focused on the client, principles of ethnography applied to product development process and user innovation. In the latter, the client is considered as having skills not only of knowledge about market needs, but also with technological domain by experience in product use and ability to generate ideas and new applications for new products. Based on these precedings the research proposal on the integration of customers in product development process appeared. This thesis aims at proposing a process for managing the customer‟s integration in the product development process in companies of capital goods. The subsidies for elaborating the proposal derived from a literature review and field research, which included case studies in five companies. The process for the customer integration is composed of three macrophases and six phases. Each phase involves activities, specific tasks and use of techniques and tools to support realization of activities. The macrophase of Customer Integration on Pre-Development involves the phases: Prospection of customer needs and/ or market opportunities, selection of clients for the Pre-Development and integration of customers on idea generation and/ or business opportunities. The macrophase of Customer Integration on Development involves the stages: Selection of clients for his integration in the product development and Customer Integration in the product development. The macrophase of Customer Integration on the Post-Development has as phase the evaluation of the customers integration in the product development. The results of the thesis contribute to both the theoretical knowledge on the subject and the practice of companies. From the theoretical point of view, the proposed process brings together content from various subject areas, analyzes and synthesizes, following the guiding principle of customers integration in product development process. From a practical standpoint, the proposed process assists in the organization and operationalization of customers integration activities, particularly in capital goods companies.
Keywords: Desenvolvimento de produtos; Inovação de produtos; Indústrias de bens de capital; Desenvolvimento de novos produtos; Integração de clientes; Product development process; Customer integration; Capital goods companies; Customers integration in product development process; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO::DESENVOLVIMENTO DE PRODUTO